Measuring Demand and Supply Shocks From COVID-19: An Industry-Level Analysis for India. (February 2022) - Patnaik, Anuradha
The present article attempts to decompose the COVID-19-induced shock to output and inflation of the Indian economy at the aggregate and disaggregate levels into demand and supply shocks for the period March 2020 to June 2020, using a structural Bayesian VAR model following Baumeister and Hamilton (2015, 2019). The results of the empirical analysis reveal that while the negative supply shocks dominate at the aggregate and disaggregate levels, their magnitude varies across industries. Demand shocks to output were positive in some industries like the manufacture of food products (10), textiles (13), chemicals and chemical products (20), and electrical equipment (27), but were outweighed by the negative supply shocks. In response to the COVID-19 shock the government announced the three pronged Atmanirbhar Bharat Abhiyan (ABA), which is a blend of demand management, supply management and structural policies. It not only promises to address the short-term distress caused to the industries due to the COVID-19 shock but also attempts to make them self-reliant and resilient to such shocks in future. JEL Classification: E10, C32, C40, E30